Das Recht auf Asyl bei Emer de Vattel 1758: unvollkommenes Recht, vollkommenes Recht, Menschenrecht - Keil, Rainer (Rechtsphilosophie, 2021)
When, within the framework of a highly controversial debate of the early 1990s in Germany on the right to asylum, Winfrid Brugger argued, a human right to asylum could not be based on sound reason, he referred to the supposed impossibility of an imputation of the plight of refugees to certain foreign states. In more recent debates, similar arguments have been brought forward and formulated as a problem of imperfect or perfect duties and rights. Much earlier, in 1758, Emer de Vattel already had discussed the right to asylum as a right that has aspects of both an imperfect right and a perfect right. This has mostly been ignored in the recent debate. In this article, I try to show how de Vattel reasoned. His argumentation limited the otherwise strong sovereignty of states by referring to the reasons of the moral legitimacy of their powers. This led him to the result that the per se perfect right to asylum, imperfect in relation to specific states, can, if states collectively fail to admit a refugee in urgent danger, become a claim against a specific country in the shape of a perfect right to self-help. I will briefly try to reconstruct some of de Vattel‘s ideas with concepts of Ronald Dworkin and Robert Alexy. The difference between Dworkin’s rule and Alexy’s Regel becomes relevant for understanding de Vattel’s perfect and human right to asylum. In the end, I will briefly investigate how much of de Vattel’s thought depends on assumptions a XXIst century thinker would probably not be ready to suppose any more. It will become clear that de Vattel’s thought on asylum is mostly independent from rather controversial assumptions of his work; it fits rather well to some recent approaches limiting sovereignty by human rights and concepts of territorial justice.
Gesehen am 29.10.2021